2013
DOI: 10.1016/j.det.2013.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Autoinflammatory Pustular Neutrophilic Diseases

Abstract: SYNOPSIS The inflammatory pustular dermatoses constitute a spectrum of non-infectious conditions ranging from localized involvement to generalized disease with associated acute systemic inflammation and multi-organ involvement. Despite the variability in extent and severity of cutaneous presentation, each of these diseases is characterized by non-infectious neutrophilic intra-epidermal microabscesses. Many share systemic findings including fever, elevated inflammatory markers, inflammatory bowel disease and/or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
114
1
26

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(148 citation statements)
references
References 218 publications
(253 reference statements)
1
114
1
26
Order By: Relevance
“…IL-36 RN mutations can be found in patients with generalized pustular psoriasis [10,11] and in rare patients with ACH [12,13,14,15]. It has been hypothesized that such mutations could be associated with the response of generalized pustular psoriasis [12] or ACH [9] to anakinra [13,14], but this has not been demonstrated [14,16]. Indeed, IL-36RN gene mutations do not account for all cases of pustular psoriasis [13,14,17,18]; moreover, the consequences of IL-36RA deficiency on the expression of pro-inflammatory cytokines are not fully known, and, although IL-36RA deficiency may induce increased production of IL-1, it has not been demonstrated that IL-1 blockade was the most relevant strategy in that context [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-36 RN mutations can be found in patients with generalized pustular psoriasis [10,11] and in rare patients with ACH [12,13,14,15]. It has been hypothesized that such mutations could be associated with the response of generalized pustular psoriasis [12] or ACH [9] to anakinra [13,14], but this has not been demonstrated [14,16]. Indeed, IL-36RN gene mutations do not account for all cases of pustular psoriasis [13,14,17,18]; moreover, the consequences of IL-36RA deficiency on the expression of pro-inflammatory cytokines are not fully known, and, although IL-36RA deficiency may induce increased production of IL-1, it has not been demonstrated that IL-1 blockade was the most relevant strategy in that context [16].…”
Section: Discussionmentioning
confidence: 99%
“…Recent descriptions of auto-inflammatory syndromes secondary to deficiency of IL-1 family member receptor, namely DIRA (deficiency of the IL-1 receptor antagonist) and DITRA (deficiency of the IL-36 receptor antagonist) [9], provided a pathophysiological background to support the use of IL-1 blockade in cases of refractory pustular psoriasis. DIRA is a rare autosomal recessive auto-inflammatory disorder caused by homozygous mutation in the gene encoding for the IL-1 receptor antagonist, leading to systemic inflammation because of uncontrolled IL-1 signalling; it is characterized by perinatal onset of a pustular dermatitis similar to pustular psoriasis, skeletal involvement and elevated inflammatory markers.…”
Section: Discussionmentioning
confidence: 99%
“…Treatments serving this purpose may include: colectomy in patients with chronic ulcerative colitis, plasmapheresis or granulocyte apheresis in patients with leukemia, or thalidomide in patients with myelodysplastic syndromes. 43,44 Anti-inflammatory and immunosuppressive drugs can be effective both in PG and the underlying disease, as the example of the IL1 antagonist anakinra for PG in the context of PAPA syndrome, 45,46 and of infliximab and other anti-TNF agents in the context of Crohn's disease and ulcerative colitis. 30,42 Among the anti-TNF biologics, etanercept is the only one reported not to be effective in IBD, which should be taken into consideration when treating these patients.…”
Section: Treatment Of the Underlying Diseasementioning
confidence: 99%
“…23,41,57 Furthermore, ustekinumab (anti-IL12/IL23) has been recently used in the management of PG with good results, and anakinra (anti-IL1) induces a very good response in patients with PAPA syndrome. 11,44,46 However, since biologic therapies are relatively new, their unknown long-term side effects should be taken into consideration.…”
Section: Systemic Treatmentmentioning
confidence: 99%
“…However, the overall pathogenesis of pustular psoriasis remains unclear. On histopathological analysis, pustular psoriasis lesions reveal an intraepidermal, neutrophil-dominant infiltrate [3], suggesting that neutrophil inhibition may treat the disease.…”
Section: Introductionmentioning
confidence: 99%